Exploring student perceptions of formative research on undergraduate students: Insights and implications for higher education - Martínez, Javiera (Journal of Education and e-Learning Research, 2025)
The purpose of this study was to understand the appreciation of pedagogy students at the Universidad de Atacama regarding the formative research model offered by the university, specifically in the development of new research skills. The study aimed to analyze the common experiences narrated by students in relation to this model. The research employed a qualitative and exploratory approach following a phenomenological orientation based on Heidegger's hermeneutic phenomenological approach. Data collection instruments included semi-structured interviews and a focus group discussion. The results indicated that students' experiences with the formative research model were predominantly positive, describing the process as enriching and transformative. However, students also identified certain aspects that they perceived as hindrances that limited possibilities for improvement. These perceived limitations highlight the need for continued refinement of the model to better address student needs and expectations. The analysis of the results uncovers significant implications suggesting that the phenomenon studied holds potential for the integral development of future professionals through curricular transformations. The findings underscore the necessity for ongoing adjustments and enhancements in the formative research model to better equip students with the skills required for research, thereby contributing to the broader educational landscape and fostering a more robust educational framework.